Rebuilding Britain: Restoring confidence, competitiveness and compassion - David Owen (Institute of Economic Affairs (IEA), 2023)
Corporation Tax hike not the path to a competitive and compassionate Britain, says former SDP Leader - Britain needs a fundamental review of many of our key institutions, from the Treasury to the NHS; - Compassion, particularly in the form of government spending, has to be paid for; - This means stopping the tax assault on business, whether through the rise in corporation tax to 25% or windfall taxes. Writing for the Institute of Economic Affairs, former Foreign Secretary and Social Democratic Party Leader Lord David Owen argues that if Britain is to become both more competitive and compassionate then the Government needs to show the country is open for business. This means first that the planned corporation tax increase should be cancelled, and also that the Government's constant flirtation with windfall taxes must end. Compassion for the poorest can only occur with a vibrant and growing economy, and we should be celebrating those who are creating the wealth which funds this support. However, the current British malaise requires more fundamental reform as well. From the Treasury to the NHS to Parliament itself, the British state needs radical reform to make it more accountable to the public. IEA Director General Mark Littlewood said: "Lord Owen is correct that the British state needs a radical overhaul. Britain today faces the highest tax burden since Clement Attlee was Prime Minister, a complex tax code thirteen times the length of War and Peace, and a civil service that focuses on looking at ways to redistribute, rather than grow, the wealth of the nation. "If we want a compassionate society, we need to pay for it. This means a vibrant and growing economy. "The Chancellor should review his plans to raise Corporation Tax and instead use his Budget to introduce pro-growth measures that will encourage businesses to our shores."
Keywords: 330; Business taxation; Economic policy; Great Britain; Unternehmensbesteuerung; Wirtschaftspolitik; Großbritannien